2023
DOI: 10.3389/fendo.2022.1098492
|View full text |Cite
|
Sign up to set email alerts
|

Association between triglyceride glucose index and risk of cancer: A meta-analysis

Abstract: BackgroundTriglyceride glucose (TyG) index as a more convenient and reliable predictor of insulin resistance (IR) is thought to be associated with many diseases, but its relationship with cancer remains unclear.MethodsThe meta-analysis was conducted to evaluate the effects of TyG index on cancer risk utilizing the available evidence. PubMed, EMBASE, Medline, Cochrane Library and Web of Science were searched from their inception up to July 2022. A random-effects model was used to calculate the effect estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…It is well known that TyG index has been used as a useful method to detect insulin resistance 14 , and it has recently been reported to be strongly associated with diseases such as diabetes and coronary heart disease 15,16 .Recently, several reports have shown that the TyG Index can predict the risk of many types of cancer 17 .A report analyzing 774 patients with endometrial cancer reported that TyG index was strongly linked to the development and progression of endometrial cancer 18 .A cohort study of 27,944 participants showed that TyG index was strongly associated with the risk of colorectal cancer 13 .Recently,as shown in many epidemiologic and clinical studies, metabolic dysfunction is recognized as a risk factor for poor cancer prognosis 19 .And insulin resistance is considered to be one of the important causes of metabolic dysfunction 20 .Therefore, in order to address this point, we further analyzed the correlation between the TyG index and the three-year prognosis and progression among patients, and concluded that there is a relevance of elevated TyG index to the poor prognosis of colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that TyG index has been used as a useful method to detect insulin resistance 14 , and it has recently been reported to be strongly associated with diseases such as diabetes and coronary heart disease 15,16 .Recently, several reports have shown that the TyG Index can predict the risk of many types of cancer 17 .A report analyzing 774 patients with endometrial cancer reported that TyG index was strongly linked to the development and progression of endometrial cancer 18 .A cohort study of 27,944 participants showed that TyG index was strongly associated with the risk of colorectal cancer 13 .Recently,as shown in many epidemiologic and clinical studies, metabolic dysfunction is recognized as a risk factor for poor cancer prognosis 19 .And insulin resistance is considered to be one of the important causes of metabolic dysfunction 20 .Therefore, in order to address this point, we further analyzed the correlation between the TyG index and the three-year prognosis and progression among patients, and concluded that there is a relevance of elevated TyG index to the poor prognosis of colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, MetS, which is closely related to IR, was not identified in 2 meta-analyses as a factor promoting the development of lung cancer [ 83 , 84 ]. However, the triglyceride glucose index (TyG), a more convenient index of IR, was proven to be related to cancer risk (RR = 1.14, 95% CI 1.08–1.20, P < 0.001) [ 85 ]. Our study found a high positive association between IR and lung cancer risk in 463 lung cancer patients out of 1,175 participants.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a metabolic disorder and has the characteristics of decreased insulin secretion and/or insulin resistance (IR) 1,14 . According to existed researches, IR increases the risk of various types of cancer, such as prostate cancer, 15 non‐small cell lung cancer, 16 gastric cancer, 17 and obesity‐related cancers 18 . And it is also associated with a higher mortality rate 19 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 14 According to existed researches, IR increases the risk of various types of cancer, such as prostate cancer, 15 non‐small cell lung cancer, 16 gastric cancer, 17 and obesity‐related cancers. 18 And it is also associated with a higher mortality rate. 19 However, it remains unclear whether IR is correlated with patients' prognosis for PC patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%